Neuroendocrine carcinomas of the gastrointestinal tract : Morphology, molecular pathology, cellular origin - Jesinghaus, Moritz (Pathologie (Heidelberg, Germany), 2024)
Neuroendocrine carcinomas (NEC) are poorly differentiated neuroendocrine neoplasms that can occur ubiquitously in the mucosa-bearing organs of the gastrointestinal tract. Based on their morphology, they are classified into large cell (LCNEC) and small cell NEC (SCNEC). The most common form of mixed differentiation is the combination with an adenocarcinoma, referred to as mixed adenoneuroendocrine carcinoma (MANEC). NEC/MANEC exhibit a significantly poorer prognosis than the adenocarcinomas of their respective primary sites, which is inextricably linked to their typical histomorphology. Adenocarcinomas with aberrant expression of neuroendocrine markers do not show a worse clinical course. Molecularly, NEC/MANEC have a profile comparable to the adenocarcinomas of their site of origin and a profile divergent from neuroendocrine tumors. Analyses of gastric NEC/MANEC have shown frequent MYC amplifications, which are reflected in MYC signatures in various transcriptome analyses.The cellular origin of NEC remains a subject of controversial discussion. New insights are provided by a MYC-driven, genetically modified mouse model that led to the development of large gastric tumors. These tumors were histologically identified as LCNEC and were accompanied by both neuroendocrine and non-neuroendocrine precursor lesions. Using immunofluorescence, a derivation from resident neuroendocrine cells in the gastric corpus was demonstrated, suggesting that at least a portion of LCNEC may originate directly from neuroendocrine cells.